2020
DOI: 10.22437/ppd.v8i2.9106
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural output and government expenditure in Nigeria

Abstract: The study empirically investigate the link between agricultural output growth and government spending in Nigeria from 1981 to 2018. Augmented Dickey-Fuller (ADF) test was used to investigate stationary variable at different levels. The mixture in order of integration necessitate Auto Redistributed Lag (ARDL) and Bounds co-integration, since it allows combination of fractionally integrated variables. The results show both short and long run effect of government spending on the growth of agricultural output in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…This inconsistency could potentially contribute to food insecurity. This is in line with Keji and Efuntade (2020), who found that disruption in government spending in the agricultural sector would have an adverse effect on agricultural output growth. If exchange rates are highly uncertain, it can affect the cost of imported goods, including food (Oluyemi and Essi 2017).…”
Section: Short-run Asymmetric Effects Of Economic Policy Uncertainty ...supporting
confidence: 90%
“…This inconsistency could potentially contribute to food insecurity. This is in line with Keji and Efuntade (2020), who found that disruption in government spending in the agricultural sector would have an adverse effect on agricultural output growth. If exchange rates are highly uncertain, it can affect the cost of imported goods, including food (Oluyemi and Essi 2017).…”
Section: Short-run Asymmetric Effects Of Economic Policy Uncertainty ...supporting
confidence: 90%
“…According to Solow & Swan (1956), as cited in the works of Wells (2015) and Keji & Efuntade (2020), long-run aggregate economic growth can be achieved through technological progress, which revolves around social infrastructural growth. The neoclassical posited that improvement in technology is capable of prompting productivity function upward, which brings about overall growth in an economy.…”
Section: Methodsmentioning
confidence: 99%
“…Abu & Abdullahi (2010) argued from other fiscal perspectives and submitted that any increase in inflation and general spending results in slow economic growth. Conversely, Keji & Efuntade (2020) argued that a general increase in output level, specifically in a steady form over a specific period, brings about the desired economic growth in Nigeria. Since economic growth is classified as the level of increase in the nation's per capita output, aided by a continuous rise in an infrastructural set-up that predates the overall consumption, trade volume, labor force, and capital (Jhingan, 2003), it is surprising that, despite the yearly budgetary provision for government spending on infrastructural development in Nigeria, the infrastructure remains a deficit, making it difficult to achieve the required economic growth in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations